Amalgamating players, symmetry and the Banzhaf value - André Casajus (Bielefeld University, Institute of Mathematical Economics (IMW), 2010)
We suggest new characterizations of the Banzhaf value without the symmetry axiom, which reveal that the characterizations by Lehrer (1988, International Journal of Game Theory 17, 89-99) and Nowak (1997, International Journal of Game Theory 26, 127-141) as well as most of the characterizations by Casajus (2010, Theory and Decision, forthcoming) are redundant. Further, we explore symmetry implications of Lehrer's 2-efficiency axiom.
Keywords: C71; 330; Banzhaf value; amalgamation; symmetry; 2-efficiency; Shapley-Wert; Kooperatives Spiel; Theorie